The Baltic Chain’s Political Impact and Memory Politics - Viktoria Mazur (Pasado y Memoria, 2025)
The Baltic Chain, a historic act of peaceful resistance, played a crucial role in the independence movements of Estonia, Latvia, and Lithuania. This article examines its impact on the dissolution of Soviet authority in the Baltic region and its evolution into a powerful symbol of unity and self-determination. Utilizing a qualitative historical approach, the study highlights the shared experiences of Baltic states under Soviet rule, the strategic use of nonviolent movements, and the global resonance of the Baltic Chain in advancing their demands for sovereignty. The research explores the event’s sociopolitical background, the involvement of grassroots organizations, and the critical role of international attention. It also addresses the mystification of the Baltic Chain through memory politics and its enduring influence on global democratic movements. While celebrating its legacy, the study acknowledges the complexities of post-independence challenges, such as economic transitions and integration of Russian-speaking minorities. By situating the Baltic Chain within the broader framework of peaceful resistance, this article contributes to understanding how collective memory and symbolic action can shape political transformation and historical narratives. Additionally, it highlights the interplay between grassroots activism, international diplomacy, and cultural identity in forging a cohesive movement that transcended national boundaries, serving as a model for other struggles for self-determination and human rights worldwide.